Salvage urethroplasty using skin grafts for previously failed long‐segment urethral strictures. Issue 9 (6th August 2016) - Sevinc, Cuneyd; Balaban, Muhsin; Ozkaptan, Orkunt; Kutlu, Necmettin; Karadeniz, Tahir
Abstract: The aim of this study was to describe a technique using full‐thickness skin grafts (FTSGs) from different parts of the body for salvage urethroplasties and the present outcomes. A total of 24 men underwent urethroplasties for strictures averaging 7.7 cm (range, 5–17 cm) in length, using FTSGs from the inner arm, inner thigh, or abdominal skin. Each of these cases had at least one failed urethroplasty. Twenty‐four patients underwent surgery for 26 urethral strictures, with a mean follow‐up period of 23.2 (5–44) months and a mean operation time of 140 (115–180) minutes. Reconstruction of the urethra with skin grafting was successful in 18 out of the 26 procedures during the first attempt (69%). A "redo" skin grafting was performed for the eight failed cases, with four successful procedures (50%). Overall, the success rate was 84% (22 out of 26 urethral strictures); however, the failed cases developed abscesses and later, ureterocutaneous fistulas. No hair formation from the skin grafts was seen. Skin grafts provide useful alternative graft sources for previously failed long‐segment urethral strictures in which the buccal mucosae are not available or are insufficient for salvage urethroplasties with an acceptable success rate.